The quadratic formula for an equation in the form:
color(white)("XXX")color(red)(a)x^2color(blue)(+b)x+color(green)(c)=0
gives us the solutions:
color(white)("XXX")x=(-color(blue)(b)+-sqrt(color(blue)(b)-4(color(red)(a)color(green)(c))))/(2color(red)(a))
x^2-175=0 is equivalent to
color(white)("XXX")color(red)(1)x^2+color(blue)(0)x+color(green)(""(-175))=0
So the solutions are
color(white)("XXX")x=(-color(blue)(0)+-sqrt(color(blue)(0)-4 * (color(red)(1) * color(green)(""(-175)))))/(2 * color(red)(1))
color(white)("XXXX")=+-sqrt(700)/2
color(white)("XXXX")=+-(10sqrt(7))/2
color(white)("XXXX")=+-5sqrt(7)